Annegret Marx, When Images Travel to Ethiopia … Impact of the Evangelium Arabicum printed 1590 in Rome on a 17th Century Ethiopian Gospel: Documentation and Synoptic Presentation of their Images - Jacopo Gnisci (Aethiopica, 2023)
Review